Supported catalyst material and preparation method thereof

Through microwave hydrothermal method and heat treatment technology, a MoP@MoO2-supported catalyst was prepared, which solved the problem of uneven distribution of MoP catalysts, achieved the formation of multi-stage pore structures and the exposure of active sites, improved the catalytic performance, and reduced the Process complexity and cost.

CN119158602APending Publication Date: 2024-12-20NINGBO ORIENTAL UNIV OF TECH (TEMPORARY NAME)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411142752.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

It is difficult to synthesize MoP catalysts with a large number of active sites by a simple method, and MoP is unevenly distributed on carriers such as carbon-based and sulfides, which affects the improvement of catalytic performance.

Method used

Nanoflake MoO3 was synthesized by microwave hydrothermal method, then mixed with sodium hypophosphite and potassium hypophosphite to carry out heat treatment under an argon atmosphere, and a multi-stage pore structure was etched by phosphide gas to form a MoP@MoO2-supported catalyst to achieve The uniform distribution of MoP on the MoO2 carrier and the core-shell structure are formed.

Benefits of technology

The multi-stage pore core-shell structure preparation of MoP@MoO2 supported catalyst is realized, providing a large number of active sites, and the process is simple and low cost. MoP is evenly distributed on the MoO2 support, improving catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158602A_ABST
    Figure CN119158602A_ABST
Patent Text Reader

Abstract

The invention provides a supported catalyst material and a preparation method thereof, and relates to the technical field of catalytic materials. The preparation method of the supported catalyst material provided by the invention comprises the following steps: firstly, synthesizing nano flaky MoO3 by adopting a microwave hydrothermal method, then sufficiently grinding and mixing sodium hypophosphite and / or potassium hypophosphite with the flaky MoO3, and carrying out heat treatment in an argon atmosphere to obtain the MoP-MoO2 supported catalyst material with the hierarchical pore core-shell structure. The preparation method of the supported catalyst provided by the invention does not need a template agent, the process is simple, the cost is low, the prepared MoP-coated MoO2 supported catalyst material with the hierarchical pore core-shell structure can provide a large number of active sites, and MoP is uniformly distributed on the MoO2 carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and in particular to a supported catalyst material and a preparation method thereof. Background Art

[0002] Transition metal phosphides (such as MoP, FeP, CoP and Ni2P) are abundant and low-cost, and are considered to be good catalysts. Among them, molybdenum phosphide (MoP) has the characteristics of Pt-like electronic structure, excellent catalytic performance and high stability, and has been proven to be a very promising hydrogen evolution catalyst. However, it is still a challenge to construct MoP nanostructures that can expose a large number of active sites. MoP-supported catalysts, such as MoP@Mo2C@C, MoP@CdS nanorods, etc., as heterojunction catalysts with abundant active sites, significantly improve the catalytic activity. However, MoP is unevenly distributed on carbon-based and sulfide carriers and is easy to agglomerate, which is not conducive to further improvement of catalytic performance. Hierarchical porous materials can provide a larger specific surface area in catalytic reactions, increase the exposure of active sites, and different pore sizes can also accelerate the mass transfer process of reaction substrates. Therefore, hierarchical porous materials have great potential in catalytic reactions. The preparation of hierarchical porous materials generally relies on template methods, including hard template methods and soft template methods, but the template method preparation steps are cumbersome, the conditions are harsh, and it is difficult to control.

[0003] Therefore, how to synthesize MoP catalysts with a large number of active sites through a simple method is an urgent problem that needs to be solved. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a supported catalyst material and a method for preparing the same. The prepared supported catalyst material MoP@MoO2 has a multi-level porous core-shell structure, can provide a large number of active sites, and MoP is evenly distributed on the MoO2 carrier. The preparation method of the supported catalyst material does not require a template, has a simple process and low cost.

[0005] The present invention provides a method for preparing a supported catalyst material, comprising the following steps: S1, molybdenum powder is subjected to microwave hydrothermal reaction in a solution containing hydrogen peroxide to obtain nano-sheet MoO3; S2, the nano-sheet MoO3 in step S1 is mixed with sodium hypophosphite and / or potassium hypophosphite, and then ground to obtain a mixture; S3, the mixture of step S2 is heat-treated in an argon atmosphere, the heat-treatment temperature is 200-500° C., and a MoP@MoO2 supported catalyst material with a multi-level porous core-shell structure is obtained.

[0006] The preparation method of the supported catalyst material provided by the present invention first adopts a microwave hydrothermal method to synthesize nano-sheet MoO3, then sodium hypophosphite and / or potassium hypophosphite are fully ground and mixed with the sheet MoO3, and heat-treated under an argon atmosphere. Sodium hypophosphite and potassium hypophosphite will gradually decompose to produce phosphine gas during the heat treatment process, and the phosphine gas will gradually etch the surface of MoO3 from the outside to the inside to form molybdenum phosphide. At the same time, under the action of corrosion and reduction, the morphology of the MoO3 nanosheet changes, rich multi-level pores are generated, and it is reduced to MoO2, thereby obtaining a MoP@MoO2 supported catalyst material with a multi-level pore structure, and because the etching process is carried out from the outside to the inside, MoP in the MoP@MoO2 supported catalyst material covers MoO2 to form a core-shell structure. The preparation method of the supported catalyst provided by the present invention does not require a template agent, has a simple process, and is low in cost. The prepared MoP@MoO2 supported catalyst material with a multi-level pore core-shell structure can provide a large number of active sites, and MoP is evenly distributed on the MoO2 carrier.

[0007] In a possible implementation, in the solution of step S1, the volume ratio of the solvent of the solution to the hydrogen peroxide is 4:1 to 6:1.

[0008] In a possible implementation manner, the solvent of the solution in step S1 is anhydrous ethanol.

[0009] In a possible implementation, the concentration of the molybdenum powder in the solution in step S1 is 5-10 g / L.

[0010] In a possible implementation, the temperature of the microwave hydrothermal reaction in step S1 is 130-150°C.

[0011] In a possible implementation manner, the microwave hydrothermal reaction time in step S1 is 2 to 4 hours.

[0012] In one possible implementation, the mass ratio of the nano-sheet MoO3 to sodium hypophosphite and / or potassium hypophosphite in step S2 is 1:1 to 1:5. The ratio of MoP to MoO2 and the pore structure can be controlled by adjusting the amount of sodium hypophosphite and / or potassium hypophosphite.

[0013] In a possible implementation, the flow rate of the argon gas in step S3 is 100-200 mL / min.

[0014] In a possible implementation manner, the heat treatment time in step S3 is 1 to 5 hours.

[0015] The present invention also provides a supported catalyst material, which is prepared by the above-mentioned supported catalyst material preparation method, and the supported catalyst material is a MoP@MoO2 supported catalyst material with a multi-level porous core-shell structure.

[0016] The reagents and raw materials used in the present invention are commercially available.

[0017] The positive and progressive effects of the present invention are: The preparation method of the supported catalyst material provided by the present invention adopts an in-situ phosphating method to corrode flaky MoO3, create pores on its surface and grow MoP in-situ to form a multi-level porous core-shell structure MoP@MoO2 material, which has the advantages of simple production steps, low cost, and green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The XRD diagrams of the supported catalyst materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown.

[0019] Figure 2 This is the SEM image of the supported catalyst material prepared in Example 1.

[0020] Figure 3 This is the SEM image of the supported catalyst material prepared in Example 2.

[0021] Figure 4 This is the SEM image of the supported catalyst material prepared in Example 3.

[0022] Figure 5 This is the SEM image of the supported catalyst material prepared in Example 4.

[0023] Figure 6 This is the SEM image of the catalyst material prepared in Comparative Example 1.

[0024] Figure 7 This is the SEM image of the supported catalyst material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0026] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0027] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0028] Example 1

[0029] This embodiment provides a supported catalyst material, which is prepared by the following preparation method: (1) Pour 85 mL of anhydrous ethanol and 15 mL of hydrogen peroxide into a beaker and mix them thoroughly using electromagnetic stirring at room temperature to obtain a solution containing hydrogen peroxide; (2) Add 720 mg of molybdenum powder to the solution obtained in step (1), and stir at room temperature for 1 to 3 hours to obtain a transparent bright yellow solution; (3) Pour the solution obtained in step (2) into a 250 mL high-pressure reactor equipped with a microwave hydrothermal instrument, set the microwave hydrothermal heating program to raise the temperature in the reactor to 150° C., and react at this temperature for 2 h. After the reaction is completed, wait for the reactor to cool naturally to room temperature, take out the product in the reactor, and obtain a crude product; (4) The crude product obtained in step (3) was centrifuged and filtered, washed with ethanol three times, and dried in a constant temperature oven at 60°C for 8 h to obtain a dark blue powder, namely, nano-sheet MoO3; (5) 0.2 g of the nano-flaky MoO3 powder obtained in step (4) and 0.2 g of sodium hypophosphite particles were mixed and ground evenly, placed in a tubular furnace, introduced with 200 mL / min of argon gas, treated at 300°C for 2 h, and naturally cooled to room temperature after the reaction. The powder after the reaction was taken out and washed with deionized water until neutral, filtered, and placed in a 60°C constant temperature box for drying for 8 h to obtain a multi-level porous core-shell structure MoP@MoO2 material.

[0030] Example 2

[0031] This embodiment provides a supported catalyst material. The difference from Embodiment 1 is that in step (5), the amount of sodium hypophosphite used is 0.4 g.

[0032] Example 3

[0033] This embodiment provides a supported catalyst material. The difference from Embodiment 1 is that in step (5), the amount of sodium hypophosphite used is 0.6 g.

[0034] Example 4

[0035] This embodiment provides a supported catalyst material. The difference from Embodiment 1 is that in step (5), the amount of sodium hypophosphite used is 0.8 g.

[0036] Example 5

[0037] This embodiment provides a supported catalyst material, which is prepared by the following preparation method: (1) Pour 60 mL of anhydrous ethanol and 15 mL of hydrogen peroxide into a beaker and mix them thoroughly using electromagnetic stirring at room temperature to obtain a solution containing hydrogen peroxide; (2) Add 375 mg of molybdenum powder to the solution obtained in step (1), and stir at room temperature for 1 to 3 hours to obtain a transparent bright yellow solution; (3) Pour the solution obtained in step (2) into a 250 mL high-pressure reactor equipped with a microwave hydrothermal instrument, set the microwave hydrothermal heating program to raise the temperature in the reactor to 130° C., and react at this temperature for 4 hours. After the reaction is completed, wait for the reactor to cool naturally to room temperature, take out the product in the reactor, and obtain a crude product; (4) The crude product obtained in step (3) was centrifuged and filtered, washed with ethanol three times, and dried in a constant temperature oven at 60°C for 8 h to obtain a dark blue powder, namely, nano-sheet MoO3; (5) 0.2 g of the nano-flaky MoO3 powder obtained in step (4) and 0.6 g of sodium hypophosphite particles were mixed and ground evenly, placed in a tubular furnace, introduced with 100 mL / min of argon gas, treated at 200°C for 5 h, and naturally cooled to room temperature after the reaction. The powder after the reaction was taken out and washed with deionized water until neutral, filtered, and placed in a 60°C constant temperature box for drying for 8 h to obtain a multi-level porous core-shell structure MoP@MoO2 material.

[0038] Example 6

[0039] This embodiment provides a supported catalyst material, which is prepared by the following preparation method: (1) Pour 85 mL of anhydrous ethanol and 15 mL of hydrogen peroxide into a beaker and mix them thoroughly using electromagnetic stirring at room temperature to obtain a solution containing hydrogen peroxide; (2) Add 720 mg of molybdenum powder to the solution obtained in step (1), and stir at room temperature for 1 to 3 hours to obtain a transparent bright yellow solution; (3) Pour the solution obtained in step (2) into a 250 mL high-pressure reactor equipped with a microwave hydrothermal instrument, set the microwave hydrothermal heating program to raise the temperature in the reactor to 150° C., and react at this temperature for 4 hours. After the reaction is completed, wait for the reactor to cool naturally to room temperature, take out the product in the reactor, and obtain a crude product; (4) The crude product obtained in step (3) was centrifuged and filtered, washed with ethanol three times, and dried in a constant temperature oven at 60°C for 8 h to obtain a dark blue powder, namely, nano-sheet MoO3; (5) 0.2 g of the nano-flaky MoO3 powder obtained in step (4) and 1 g of sodium hypophosphite particles were mixed and ground evenly, placed in a tubular furnace, introduced with 200 mL / min of argon gas, treated at 500°C for 1 h, and naturally cooled to room temperature after the reaction. The powder after the reaction was taken out and washed with deionized water until neutral, filtered, and placed in a 60°C constant temperature box for drying for 8 h to obtain a multi-level porous core-shell structure MoP@MoO2 material.

[0040] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 only has steps (1) to (4) but no step (5).

[0041] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in step (5) of Comparative Example 2, H2 is used to reduce the nano-sheet MoO3 at high temperature to prepare bulk MoO3@MoO2.

[0042] Effect test Figure 1 The XRD diagrams of the catalyst materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown. Figure 1 In the embodiment 1, the diffraction peak corresponds to MoO2 and MoP, and the diffraction peak of comparative example 1 corresponds to pure MoO3 crystal. Compared with comparative example 1, the diffraction peak intensity of embodiment 1 is weaker, indicating that the crystallinity is weakened, which may be related to the rich pore structure of the material; while the diffraction peak of comparative example 2 corresponds to Mo4O 11 and MoO2, indicating that compared with sodium hypophosphite, the reducing ability of hydrogen on flaky MoO3 is poorer.

[0043] Figure 2 This is a SEM image of the supported catalyst material prepared in Example 1. As can be seen from the image, the supported catalyst material prepared in Example 1 is mainly in a sheet-like structure, with small pores of different sizes appearing on the surface.

[0044] Figure 3 This is a SEM image of the supported catalyst material prepared in Example 2. As can be seen from the image, the supported catalyst material prepared in Example 2 shows more pores in its morphology, and its pore walls are thicker.

[0045] Figure 4 This is a SEM image of the supported catalyst material prepared in Example 3. As can be seen from the image, the pore structure of the supported catalyst material prepared in Example 3 is richer and its stacking is denser.

[0046] Figure 5This is a SEM image of the supported catalyst material prepared in Example 4. As can be seen from the figure, the supported catalyst material prepared in Example 4 has the richest pore structure. Due to excessive etching, its stacking is loose, and the pore diameters are mostly in the range of 0.5-1.5 μm.

[0047] Figure 6 This is a SEM image of the catalyst material prepared in Comparative Example 1. As can be seen from the figure, the MoO3 prepared in Comparative Example 1 has a smooth flaky morphology.

[0048] Figure 7 This is a SEM image of the supported catalyst material prepared in Comparative Example 2. As can be seen from the figure, the catalyst material prepared in Comparative Example 2 presents a block structure with a smooth surface, indicating that the reduction effect of hydrogen has no pore-forming ability on the flake MoO3.

[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a supported catalyst material, characterized in that: The following steps are involved: S1, molybdenum powder is subjected to microwave hydrothermal reaction in a solution containing hydrogen peroxide to obtain nano-sheet MoO3; S2, the nano-sheet MoO3 in step S1 is mixed with sodium hypophosphite and / or potassium hypophosphite, and then ground to obtain a mixture; S3, the mixture of step S2 is heat-treated in an argon atmosphere, the heat-treatment temperature is 200-500° C., and a MoP@MoO2 supported catalyst material with a multi-level porous core-shell structure is obtained.

2. The method for preparing a supported catalyst material according to claim 1, characterized in that: In the solution of step S1, the volume ratio of the solvent of the solution to the hydrogen peroxide is 4:1-6:

1.

3. The method for preparing a supported catalyst material according to claim 1, characterized in that: The solvent of the solution in step S1 is anhydrous ethanol.

4. The method for preparing a supported catalyst material according to claim 1, characterized in that: In the solution of step S1, the concentration of the molybdenum powder is 5-10 g / L.

5. The method for preparing a supported catalyst material according to claim 1, characterized in that: The temperature of the microwave hydrothermal reaction in step S1 is 130-150°C.

6. The method for preparing a supported catalyst material according to claim 1, characterized in that: The time of the microwave hydrothermal reaction in step S1 is 2 to 4 hours.

7. The method for preparing a supported catalyst material according to claim 1, characterized in that: In step S2, the mass ratio of the nano-sheet MoO3 to the sodium hypophosphite and / or potassium hypophosphite is 1:1 to 1:

5.

8. The method for preparing a supported catalyst material according to claim 1, characterized in that: The flow rate of argon gas in step S3 is 100-200 mL / min.

9. The method for preparing a supported catalyst material according to claim 1, characterized in that: The heat treatment time in step S3 is 1 to 5 hours.

10. A supported catalyst material, characterized in that The supported catalyst material is prepared according to the method for preparing a supported catalyst material according to any one of claims 1 to 9, and the supported catalyst material is a MoP@MoO2 supported catalyst material having a multi-level porous core-shell structure.